Estimation of lipid profile in patients with pulmonary tuberculosis: A cross-sectional observational study. - Sahu, Prasanjeet; Sahoo, Srinibas (Student's Journal of Health Research Africa, 2025)
Background A significant worldwide health concern is pulmonary tuberculosis (TB) with well-documented effects on host metabolism. Lipid disturbances, particularly hypocholesterolemia and reduced HDL cholesterol, are common in TB and may reflect both nutritional status and disease severity. Understanding these changes can aid in clinical management and nutritional intervention. Methods In this resaecrh study was carried on 101 confirmed pulmonary TB patients. Data on demographics, BMI, lifestyle habits, and radiological severity were recorded. Various lipid parameters were measured. Statistical analysis included t-tests, ANOVA, and Pearson correlation, with significance level at p<0.05. Results The mean age was 51.73 years, with 64.4% male participants. Most patients had a normal BMI, but 16.8% were underweight. Mean lipid values were: total cholesterol 156.68 mg/dL, triglycerides 137.24 mg/dL, HDL cholesterol 34.54 mg/dL, LDL cholesterol 99.38 mg/dL, and VLDL cholesterol 12.53 mg/dL. BMI correlated positively with total cholesterol and LDL cholesterol, whereas disease severity correlated negatively with HDL cholesterol. Smoking showed no significant impact on cholesterol levels. Conclusion Pulmonary tuberculosis is associated with marked lipid abnormalities, particularly hypocholesterolemia and low HDL cholesterol, more pronounced in underweight individuals and those with severe disease. Lipid monitoring may serve as an adjunctive marker for disease assessment and prognosis. Recommendation Routine lipid profile testing should be considered in TB patients, with timely nutritional support aimed at correcting hypolipidemia to enhance recovery and treatment outcomes.